How does clay constrain woody biomass in drylands?. Issue 8 (10th May 2015) - Fensham, Roderick J.; Butler, Don W.; Foley, Jenny
Abstract Aim To investigate the role of clay in limiting the development of woody biomass in drylands. Location Australia. Methods Spatial data representing woody biomass, soil clay content and climate for the Australian continent were interpreted to explore the relationship between a moisture index and woody biomass on clay and non‐clay substrates. Moisture and soil water potential were investigated through time for clay and sand plains. Sub‐soil clay and other soil characteristics were compared between areas with and without high tree mortality after drought. Results The substantially lower woody biomass on clay soils than non‐clay soils in the drylands of the Australian continent verifies the inverse texture effect. A clay floodplain consistently held more water than an adjacent sandplain, but soil moisture in the clay was effectively inaccessible to plants for much longer periods because of more negative values of water potential in the clay soil. Small increases in sub‐soil clay were associated with high tree mortality. Main conclusions Our findings suggest that the 'inverse texture effect', which describes the negative association of woody biomass with soil clay content in drylands, may mostly relate to the moisture‐retentive properties of clay rather than being caused by reduced infiltration and enhanced evaporation from clay‐rich soils. Our evidence suggests that clay soils constrain woodiness in drylands by exacerbating water stress, and confirm the fundamental role of aridity in determining woody biomass and the global distribution of grassland.